2018
DOI: 10.1111/imm.12884
|View full text |Cite
|
Sign up to set email alerts
|

CD70 encoded by modified vaccinia virus Ankara enhances CD8 T‐cell‐dependent protective immunity in MHC class II‐deficient mice

Abstract: SummaryThe immunological outcome of infections and vaccinations is largely determined during the initial first days in which antigen‐presenting cells instruct T cells to expand and differentiate into effector and memory cells. Besides the essential stimulation of the T‐cell receptor complex a plethora of co‐stimulatory signals not only ensures a proper T‐cell activation but also instils phenotypic and functional characteristics in the T cells appropriate to fight off the invading pathogen. The tumour necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Bathke et al [ 58 ] designed rMVA-CD70 constructs for homologous prime-boost experiments and observed that CD8 T cell responses against the MVA epitope B8R were stronger after CD70 co-expression via two rMVA immunizations than those against the target transgene—ovalbumin (OVA). Such misdirected effects could lead to unspecific and harmful immune reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Bathke et al [ 58 ] designed rMVA-CD70 constructs for homologous prime-boost experiments and observed that CD8 T cell responses against the MVA epitope B8R were stronger after CD70 co-expression via two rMVA immunizations than those against the target transgene—ovalbumin (OVA). Such misdirected effects could lead to unspecific and harmful immune reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, preclinical efficacy of MVA was mainly attributed to CD4 + T cells and polyclonal h5T4-specific antibodies, as only weak CD8 + T cell responses were induced ( 50 ). Therefore, the addition of stimulatory immune checkpoints like inclusion of CD70 or mGITRL-fusion proteins has been tested preclinically to enhance CTL responses ( 51 ). More robust tumor regression with improved overall survival was reported when using viral vectors encoding mGITRL-fusion proteins.…”
Section: Viral Anticancer Vaccines That Have Entered the Clinical Arementioning
confidence: 99%
“…[ 17 ] The cytotoxicity of CD8T cells is influenced by transcription factors and receptor/ligand pair. [ 18 , 19 ] For instance, a recent study revealed that Interleukin 2 treatment has the potential to enhance the function of CD8T cells. [ 20 ] In addition, the upregulation of C-X-C motif chemokine receptor 3 expression, a chemokine receptor, could promote the recognition of targets in CD8T cells.…”
Section: Introductionmentioning
confidence: 99%